2008 1st IFIP Wireless Days 2008
DOI: 10.1109/wd.2008.4812900
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the Expected Transmission Time Metric for OLSR Wireless Mesh Networks

Abstract: Abstract-This paper presents the design of a plug-in for the Optimized Link State Routing (OLSR) protocol with the Expected Transmission Time (ETT) metric and experiments in an indoor testbed. The ETT metric is implemented as a plug-in, keeping portability and facilitating its deployment on operational networks. Our design identifies important implementation issues. Additionally, we run experiments in an indoor testbed to verify the performance of our ETT plug-in. Our results show that the ETT metric has the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 9 publications
1
33
0
Order By: Relevance
“…This anticipation allows the routing protocol to compensate the delay due to the computation and dissemination of the metrics. We considered ETX [5] (Expected Transmission Count) and ETT [6] (Expected Transmission Time), but we combine their computation to our prediction algorithm. Through a large set of simulations and scenarios, we have shown that our method improves significantly the PDR.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This anticipation allows the routing protocol to compensate the delay due to the computation and dissemination of the metrics. We considered ETX [5] (Expected Transmission Count) and ETT [6] (Expected Transmission Time), but we combine their computation to our prediction algorithm. Through a large set of simulations and scenarios, we have shown that our method improves significantly the PDR.…”
Section: Resultsmentioning
confidence: 99%
“…A lot of metrics have been proposed in literature [18]. In this paper, we focus on the most popular metrics, ETX [5] and ETT [6], which have been shown among the most efficient [18]. Moreover, we present the LD (Link Duration) metric in detail as it will be used in our simulations.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…ETT metric [6], [7] is improved from ETX metric. ETT metric reflects packet loss rate, route length, and link bandwidth between nodes.…”
Section: Related Workmentioning
confidence: 99%